Qui domina el món? el poder econòmic transnacional i el poder (2006)
ABSTRACT: The suggestive and intriguing question of who rule the world is an invitation to study the world corporate network. Through the study of the intercorporative relations by interlocking directorates we try to answer two questions. First, if a transnational economic power exists, that’s to say, is there a set of corporations with transnational dynamic, relationships between the greatest and most important companies in the world. Second, if the intercorporative system is based on the financial power (banks and the insurances companies). The results show the existence of a large transnational economic power where elites are related by cultural and/or geographic proximity, as well as, a colective banking power that dominates the intercorporative system. Furthermore, we distinguish three models of transnational corporations according to its national networks: the French-German model of high international presence and compact and cohesive national corporate network. The Anglo-Saxon model has international presence and low compact national network. The Japanese model has neither transnational corporations nor cohesive corporate network.